1995
DOI: 10.1016/0029-7844(95)00086-7
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal hysterectomy by uterine morcellation: An efficient, non-morbid procedure

Abstract: Uterine size alone is not an absolute contra-indication to vaginal hysterectomy. Large uterine size (greater than 300 g) was not related to a significant increase in failed vaginal hysterectomy. Conversely, failed vaginal hysterectomy was not size-dependent. Furthermore, there is no additional operative morbidity when vaginal hysterectomy is converted to a total abdominal hysterectomy because of a technical inability to complete the surgery vaginally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 8 publications
6
30
0
3
Order By: Relevance
“…Fibroid was commonest finding in many other studies also 5,6. In another study DUB was highest 30%, followed by uterine fibroid 22% Morcellation by different technique (bisection, myomectomy, wedge debulking) to accomplish delivery of the specimen was needed in 36 cases. Usefulness of morcellation was described in many other studies also 4,8,9,10 . Adnexal surgery was performed in 12 cases without any difficulty.…”
Section: Discussionmentioning
confidence: 83%
“…Fibroid was commonest finding in many other studies also 5,6. In another study DUB was highest 30%, followed by uterine fibroid 22% Morcellation by different technique (bisection, myomectomy, wedge debulking) to accomplish delivery of the specimen was needed in 36 cases. Usefulness of morcellation was described in many other studies also 4,8,9,10 . Adnexal surgery was performed in 12 cases without any difficulty.…”
Section: Discussionmentioning
confidence: 83%
“…Now big and bulky uteri can be dealt with by techniques like bisection, myomectomy and morcellation. Davies et al 7 and Mazdisnian et al 8 described these techniques. We could remove uteri upto 16 weeks uterine size, vaginally by clampless NDVH.…”
Section: Resultsmentioning
confidence: 99%
“…Davies et al and Mazdisnian et al resorted to these techniques. 10,17 Kumar and Antony successfully carried out vaginal hysterectomies in 95% patients and 75% of their patients needed morcellation or hemisection or myomectomy. 18 Mean operating time was 92.03 min which is comparable to Magos A et al and Kovac et al which showed 84.3 and 94 minutes respectively.…”
Section: Discussionmentioning
confidence: 99%